2016
DOI: 10.1111/tan.12796
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen class II (DRB1 and DQB1) alleles and haplotypes frequencies in patients with pemphigus vulgaris among the Serbian population

Abstract: The etiology of pemphigus vulgaris (PV) is multifactorial and includes genetic, environmental, hormonal, and immunological factors. Inheritance of certain Human class II leukocyte antigen (HLA) alleles is by far the best-established predisposing factor for the development of PV. Class II HLA alleles vary among racial/ethnic backgrounds. We have determined an association between HLA class II alleles and PV among the Serbian population. A total of 72 patients with confirmed diagnosis of PV were genotyped for HLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Therefore, we only included studies where the frequency was given in absolute and relative numbers and data for allele and genotype frequency was analyzed individually. Several studies used a single control group for two different datasets, and to avoid overestimating the number of controls, data of these studies was pooled where possible 74 77 (exception: two studies from Serbia 78 , 79 ). All studies included in the meta-analysis reported that the controls and patients derived from the same geographic location or that the controls were ethnically matched to the patients, but most studies did not provide further details on the ethnical matching.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we only included studies where the frequency was given in absolute and relative numbers and data for allele and genotype frequency was analyzed individually. Several studies used a single control group for two different datasets, and to avoid overestimating the number of controls, data of these studies was pooled where possible 74 77 (exception: two studies from Serbia 78 , 79 ). All studies included in the meta-analysis reported that the controls and patients derived from the same geographic location or that the controls were ethnically matched to the patients, but most studies did not provide further details on the ethnical matching.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we only included studies where the frequency was given in absolute and relative numbers and data for allele and genotype frequency were analyzed individually. Several studies used a single control group for two different datasets, and to avoid overestimating the number of controls, data of these studies were pooled where possible [51][52][53][54] (exception: two studies from Serbia 55,56 ). All studies included in the meta-analysis reported that the controls and patients derived from the same geographic location or that the controls were ethnically matched to the controls, but most studies did not provide further details on the ethnical matching.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Therefore, we only included studies where the frequency was given in absolute and relative numbers and data for allele and genotype frequency were analyzed individually. Several studies used a single control group for two different datasets, and to avoid overestimating the number of controls, data of these studies were pooled where possible (52-55) (exception: two studies from Serbia (56,57)). All studies included in the meta-analysis reported that the controls and patients derived from the same geographic location or that the controls were ethnically matched to the controls, but most studies did not provide further details on the ethnical matching.…”
Section: Study Limitationsmentioning
confidence: 99%